Efektifitas Bioporidrainase sebagai Resapan Air - Hakim, Abdul (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
Development of cities increasing rapidly and low of green open space cause availability of soil surface for water infiltration decreasing. In Contrast, the water runoff in hight affects the puddles like in UIN Sunan Ampel Surabaya Campus in rainy season, especially after heavy rain. The aim of study is to know how many hight of puddles in drainage channel with low of gradient hydraulic value and to know soil ability in site to infiltrate water. Many tests of laboratory were conducted such as: properties soil test, permeability, and infiltration test to analysis the biodrain need in 5 (five) of drainage channel. The result show that channel C-D needs 16 biodrain, channel K-M needs 5 biodrain, channel M1-M dan P1-Q1 needs 12 biodrain, Moreover, channel Q-T needs 30 biodrain to infiltrate water to soil effectively. Keywords: Bioporedrainage, water infiltration, Runoff.